Teacher qualification and instructional delivery modes at the preschool level in Nigeria (2009)
Through this study researchers sought to evaluate the effects of qualification on instructional delivery modes of practicing preschool teachers in Nigeria. The sample consisted of 93 preschool teachers and 2,859 pupils aged 4 to 5 years. Schools were selected through stratified random sampling to ensure adequate representation of private, public, urban, and rural schools. A questionnaire and two valid and reliable classroom observational instruments were used to record instructional delivery in 216 lessons in 72 preprimary classrooms. Data analysis involved the use of frequency, percentages, t-test, chi-square, and graphical illustrations. The results revealed that none of the teachers observed had preschool education training; teacher whole-class interaction characterized by direct instruction was the prevailing approach; use of play did not feature; whole-class activity occurred more than individual pupil activity monologue, and other distracting behaviors occurred less frequently. The direction of communication was mainly from the teacher to the whole class, whereas the more personal one-to-one communication between teacher and pupil occurred less frequently.